Humanizacja w XXI wieku nowoczesnego podmiotu - Irena Grochowska (Studia Ecologiae et Bioethicae)
The crisis of sense, which affects us badly nowadays, causes us to reflect on and promote new solutions as well as create personalities fulfilling the requirements of the modern world. The answer requires a comprehensive analysis of the problem in order to present the integral vision of the man in the world. The attempt to shape the survival man and the features he should possess has its justification in the influence of the environment on the integral shaping of the man and his survival. The need for ecological reflection is caused by intensive changes in political and social life. The approach based on ecological space and eco-development requires a properly shaped and mature personality. In contemporary civilization obligations, jobs and responsibilities too often are beyond the capabilities of an individual person. The responsible, "auxiliary" functions require the integrally shaped person rather than learning the individual roles. Therefore, the important hierarchy in shaping the man has a considerable influence on the final effect, which is the "real" man. Education, formation, and then, on this foundation, training for particular roles and jobs taking into account the structure and condition of the man as well as all his internal and external conditions, may lead to the fully mature person, ready to undertake activities in agreement with the defined aims.